An olive-derived elenolic acid stimulates hormone release from L-cells and exerts potent beneficial metabolic effects in obese diabetic mice - Wang, Yao; Wu, Yajun; Wang, Aiping; Wang, Aihua; Alkhalidy, Hana; Helm, Richard; Zhang, Shijun; Ma, Hongguang; Zhang, Yan; Gilbert, Elizabeth; Xu, Bin; Liu, Dongmin (Frontiers in Nutrition, 2022)
Insulin resistance and progressive decline in functional β-cell mass are two key factors for developing type 2 diabetes (T2D), which is largely driven by overweight and obesity, a significant obstacle for effective metabolic control in many patients with T2D. Thus, agents that simultaneously ameliorate obesity and act on multiple pathophysiological components could be more effective for treating T2D. Here, we report that elenolic acid (EA), a small molecule, is such a dual-action agent. we show that EA dose-dependently stimulates GLP-1 secretion in mouse clonal L-cells and isolated mouse ileum crypts. In addition, EA induces L-cells to secrete peptide YY (PYY). EA induces a rapid increase in intracellular [Ca2+]i and the production of inositol trisphosphate in L-cells, indicating that EA activates phospholipase C (PLC)-mediated signaling. Consistently, inhibition of (PLC) or Gαq ablates EA-stimulated increase of [Ca2+]i and GLP-1 secretion. In vivo, a single dose of EA acutely stimulates GLP-1 and PYY secretion in mice, accompanied with an improved glucose tolerance and insulin levels. Oral administration of EA at a dose of 50 mg/kg/day for 2 weeks normalized the fasting blood glucose and restored glucose tolerance in high-fat diet-induced obese (DIO) mice to levels that were comparable to chow-fed mice. In addition, EA suppresses appetite, reduces food intake, promotes weight loss, and reverses perturbated metabolic variables in obese mice. These results suggest that EA could be a dual-action agent as an alternative or adjuvant treatment for both T2D and obesity.